Analisis Asimilasi Perkawinan Beda Etnis Banjar dan Jawa di Kelurahan Jayengan Solo - Fariziella Alfinda; Yanti Haryanti (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research discusses the process of cultural assimilation in an interethnic marriage between Banjar and Javanese ethnicities in Jayengan Village, Solo. This cultural assimilation has occurred since the colonial period due to interethnic migration and intermarriage. The intermingling of Banjar, Javanese and Chinese ethnicities results in a multicultural culture and social identity. The assimilation process between Banjar and Javanese ethnicities in Jayengan Village shows a uniqueness that is influenced by creative economic dynamics, Javanese cultural dominance, and regional characteristics. Using a qualitative approach and purposive sampling technique, the researcher interviewed six couples who have been married for more than five years. The results show that assimilation occurs in various aspects of life, such as language use, eating habits, traditions, parenting, as well as social and religious practices. The dominant Javanese culture in the Jayengan neighborhood affects the Banjar ethnic's adaptation process, but relationships remain harmonious thanks to open and respectful intercultural communication. An inclusive social environment also accelerates cultural acceptance of each other. This study concludes that assimilation in inter-ethnic marriages is not simply a cultural unification, but a dynamic process that shapes multicultural family identity and strengthens social harmony in a pluralistic society.